Assessment of atrial septal defects rims on transesophageal echocardiogram at Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Adhikari, Chandra Mani; Shrestha, Manish; Shakya, Urmila (Nepalese Heart Journal, 2017)
Background and Aims: Transcatheter Atrial septal defects (ASD) closure has become the better alternative to surgical closure. Morphological variations of ASD are frequent. We aim to study the rims of ASD in Transesophageal echocardiogram (TEE). Methods: It was a retrospective single center audit done at Shahid Gangalal National Heart Centre, Kathmandu, Nepal. TEE clips of all the patients who underwent TEE evaluation for ASD device closure in our centre between June to August 2017 were studied. Results: During the study period 49 patients underwent TEE to evaluate the rims of ASD for device closure. Atrioventricular rim was good in all patients but it was floppy in one patient. In four chamber view, posterior rim was good in 21(42.8%) patients, floppy in 19 (38.7%) patients and absent in nine (18.5%) patients. Aortic rim was good in 15 (30.6%) patients, floppy in three (6.1%) patients and absent in 31(63.3%) patients. Posterior rim in short axis was good in 17 (34.6%) patients, floppy in 24 (48.9%) patients while it was absent in eight (16.3%) patients. Inferior venacava rim was good in 16 (32.6%) patients, floppy in 23 (46.9%) patients, while absent in ten (20.4%) patients. Superior venacava rim was good in 45 (91.8%) patients, floppy in one (2.1%) patient and absent in three (6.1%) patients. Two (4.1%) patients had two ASDs. Conclusion: Most of the ASD patients have absent rims which makes the procedure more demanding and challenging. Nepalese Heart Journal 2017; 14(2): 35-36